Introduction: Convergence and expansion in cognitive linguistics - Brdar, Mario (Array, 2011)
The introductory chapter expounds on the the issues of convergence and expansion in cognitive linguistics. The present volume aims at reflecting on these tendencies and showing the vitality, open-endedness, and the dynamic nature of the cognitive linguistic enterprise as it converges and expands. Its chapters are divided into three parts. Part 1, “Setting the scene”, contains two overview chapters by Langacker, and Barcelona and Valenzuela, which can be seen as an extension of the present introduction, as they present two alternative views on the central theme of the present volume: convergence and expansion in cognitive linguistics, first seen from a personal perspective, and than set in a more “objective”, historical perspective. These are followed in Part 2, “Consolidating the paradigm”, by chapters that come under the rubric of convergence by Nuyts, Steen, Panther and Thornburg, Belaj, Barcelona, and Langacker. Part 3, “Expanding the paradigm”, is comprised of chapters dealing with different directions of expansion by Gibbs and Ferreira, Gries, Stefanowitsch, Tissari, Harder, and Kövecses.